Electroactive materials with tunable response based on block copolymer self-assembly - Ivan Terzic; Niels L. Meereboer; Mónica Acuautla; Giuseppe Portale; Katja Loos (Nature Communications, 2019)
Ferroelectric polymers are key building blocks for flexible electronic devices, but lack functionality and ability to tune their ferroelectric response. Here the authors show a method to introduce functionality in ferroelectric polymers while preserving ferroelectricity and tune the ferroelectric response by incorporating insulating polymer chains.